2006
DOI: 10.1074/jbc.m600026200
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Neurite Outgrowth in PC12 Cells Mediated by Connexin Hemichannels and ATP

Abstract: Gap junctions have traditionally been described as transmembrane channels that facilitate intercellular communication via the passage of small molecules. Connexins, the basic building blocks of gap junctions, are expressed in most mammalian tissues including the developing and adult central nervous system. During brain development, connexins are temporally and spatially regulated suggesting they play an important role in the proper formation of the central nervous system. In the current study, connexins 32 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 60 publications
1
55
0
Order By: Relevance
“…But argument continues, partly due to different experimental models, leading to different and even opposing results and conclusions [34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
“…But argument continues, partly due to different experimental models, leading to different and even opposing results and conclusions [34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
“…Because Ngn2 is expressed in both the INPs and the new generated postmitotic neurons (15), and there is no specific marker to distinguish the INPs and the early stage postmitotic neurons, our results could not exclude the possibility that the BrdU ϩ cells in the VZ included the new generated postmitotic neurons. In addition, recent study has shown that ATP signaling might play a role in the neuronal differentiation and process outgrowth (40), both of which are essential for the initiation of radial migration of the postmitotic neurons. The proliferative SVZ in the forebrain has a uniquely important role during the second half of intrauterine development in the human brain (5,10).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies using Cx43cKO and Cx43k258stop mice have indicated that the C terminus is required for cortical neuronal migration (30). In addition, independent regulation of the gap junction channel or C-terminal domain in neurite outgrowth (31,32) and cellular motility (33)(34)(35)(36)(37) have been demonstrated in various cell types, indicating that they may affect the neocortical development (38).…”
mentioning
confidence: 99%